A New Possible Etymology for the Classical Persian Particle mar - Rezai Baghbidi, Hassan (Journal of Iranian Linguistics, 2024)
The etymology of the Classical Persian particle mar, which is traditionally believed to have an emphatic or restrictive sense, has long been an enigma to scholars of Iranian philology and Persian linguistics, esp. because there is no trace of it in the extant Middle Persian texts. Different etymologies have so far been proposed for mar, but it is often compared with the Early Judaeo-Persian preposition azmar (i) “for” and therefore believed to have originated from the word mar “number; account”. The present paper reviews all previous studies and attempts to provide a new possible etymology, according to which mar is a focus marker derived through a grammaticalization process from the Bactrian word μαρο [mar] “here”.
Keywords: Bactrian; Classical Persian; etymology; focus marker; grammaticalization